The effects of foreign aid on refugee flows - Dreher, Axel; Fuchs, Andreas; Langlotz, Sarah (GLO discussion paper, 2018)
This article is the first to systematically study whether foreign aid affects the net flows of refugees from recipient countries. Combining refugee data on 141 origin countries over the 1976-2013 period with bilateral Official Development Assistance data, we estimate the causal effects of a country's aid receipts on both total refugee flows to the world and flows to donor countries. The interaction of donor-government fractionalization and a recipient country's probability of receiving aid provides a powerful and excludable instrumental variable, when we control for country- and time-fixed effects that capture the levels of the interacted variables. Although our results suggest that exogenous aid induces recipient governments to encourage the return of their citizens, we find no evidence that aid reduces worldwide refugee outflows or flows to donor countries in the short term. However, we observe long-run effects after four three-year periods, which appear to be driven by lagged positive effects of aid on growth.
Keywords: 1976-2013; Graue Literatur